Laboratory Course During Pandemic Covid-19: Do Lab at Home to Promote Creative Thinking Skill - Dewi, Siti Herlina; Sudarmin, Sudarmin; Haryani, Sri; Sulistyaningsih, Triastuti (International Journal of Active Learning, 2022)
During online learning, students are generally asked to study practicum procedures that have been provided by the lecturer, then they are given raw data from practicum results in the previous semester for analysis and preparation of practicum reports. Another method used is to provide demonstration videos or use digital applications such as virtual labs. In general, students can attend lectures smoothly and well, but many also say that this method is boring because there is almost no difference with theoretical classes. The object of the research is second semester chemistry students, which consists of 1 class of chemistry program and 1 class of chemistry education program. The research begins with a pretest, then students carry out the planned learning, then ends with a posttest and filling out a questionnaire. The project in the do lab at home practicum is specified to titrate a solution of vinegar with a solution of baking soda or vice versa. Each student prepares a buffer solution with various pH according to the instructions of sub-project 1, makes an acid-base indicator solution from natural materials according to the instructions of sub-project 3, and determines the RGB ratio of a buffer solution that has been given a natural acid-base indicator using the instructions of the sub-project.  In quantity, all students upload practicum videos, with a duration ranging from 8-15 minutes.  Based on the results of the practicum videos uploaded by students, the first creativity that can be seen immediately is the composition of video editing, such as sound quality, image quality, and the addition of information in the video. In this study, in general, it can be said that students are in the development stage for the fluency-brainstorming indicator.  Just like fluency indicators, flexibility indicators are also generally still in the developing stage, they still need help in taking new perspectives. Making videos, although not the main product, can train students' skills, including creative thinking. In detail, risk taking indicators are further divided into 2, namely risk taking-1 and risk taking-2. Most of the students are at the developing level for the risk taking-1 indicator.